2014
DOI: 10.1111/jvs.12181
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of fern and angiosperm herb community structure in lower montane rainforest in Indonesia

Abstract: Questions: Do ferns, which are physiologically less well adapted to conserve water than angiosperms but have more efficient propagule dispersal, show different vegetation-environment relationships than co-occurring angiosperm herbs? We hypothesized that ferns should show closer relationships to local environmental conditions and might be more closely associated with humid and shady microhabitats.Location: Pono and Bariri, two sites in lower montane primary tropical forest, Lore Lindu National Park, Central Sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
2
14
1
2
Order By: Relevance
“…While these authors did not find direct evidence of physiological differences between the two groups, they did find that community composition and species turnover between sites was tied more closely to local environmental conditions for ferns than for flowering plants. This study and many others have also shown that ferns are very sensitive to soil traits (Karst et al., ; Zuquim et al., , ; Jones et al., , ; Tuomisto et al., ; Lehtonen et al., ), which can vary extensively over small spatial scales. If ferns are highly sensitive to local environmental and soil conditions, we might expect these abiotic factors to override competitive interactions in terms of importance at the local scale.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…While these authors did not find direct evidence of physiological differences between the two groups, they did find that community composition and species turnover between sites was tied more closely to local environmental conditions for ferns than for flowering plants. This study and many others have also shown that ferns are very sensitive to soil traits (Karst et al., ; Zuquim et al., , ; Jones et al., , ; Tuomisto et al., ; Lehtonen et al., ), which can vary extensively over small spatial scales. If ferns are highly sensitive to local environmental and soil conditions, we might expect these abiotic factors to override competitive interactions in terms of importance at the local scale.…”
Section: Discussionsupporting
confidence: 66%
“…Jones et al. () reached this conclusion in a study of fern and angiosperm herb‐layer communities in Indonesia. While these authors did not find direct evidence of physiological differences between the two groups, they did find that community composition and species turnover between sites was tied more closely to local environmental conditions for ferns than for flowering plants.…”
Section: Discussionmentioning
confidence: 86%
“…Herbaceous plants represent a significant proportion of the forest biodiversity, but they remain largely understudied despite their ecological relevance: they contribute to ecological processes, serve as ecological indicators of habitat quality and provide food and shelter for numerous wildlife species (reviewed in Ruben, Bolger, Peart, & Ayres, ; Wyatt & Silman, ; Jones, Cicuzza, van Straaten, Veldkamp, & Kessler, ; Willie, Tagg, Petre, Pereboom, & Lens, ). Studies on herbaceous plant abundance, distribution, diversity and composition in forest stands at different successional stages can inform biodiversity conservation policy and forest management practices (Allen, Platt, & Coker, ; Duffy & Meier, ; Fraser, Jentsch, & Sternberg, ; Willie, ; Wyatt & Silman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Herbaceous plant species diversity and composition are affected by forest structure, tree species composition and topographic and environmental variables (Akhtar & Bergmeier, ; Berger & Puettmann, ; Ellum, Ashton, & Siccama, ; Jones et al., ; McKenzie, Halpern, & Nelson, ). In habitats such as light gaps, herbaceous plant species richness or density can be high due to a conducive environment (Qin et al., ; Willie, Petre, Tagg, & Lens, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation